Mass movements dynamics and morphologies in Costa Rica - Quesada Román, Adolfo (2024)
Landslides are natural processes that commonly affect human activities at every latitude and altitude worldwide. Tropical countries such as Costa Rica deal annually with landslides affecting public and privateinfrastructure and activities. This chapter provides a brief overview of landslide origin, dynamics, and morphologies applicable to Costa Rica. Coseismic and hydrometeorological dynamics are common landslide triggers, but land use changes are also important. Large landslides are related with volcanic slopes and densely vegetated rural contexts, while smaller but more common mass movements are linked with periurban conditions, especially in densely populated areas with altered land use. On average, during the last five decades every year, 80 landslide events occurred in Costa Rica, causing 5 people died, 9 houses destroyed, and approximately, 1 million US dollars of losses. This chapter suggests more tudies dealing with modelling, geomorphological characterization, early warning systems, and continued monitoring of landslides on susceptible sites in Costa Rica.